Saturated Linkers in Two-Dimensional Covalent Organic Frameworks Boost Their Luminescence - Yang, Meijia; Hanayama, Hiroki; Fang, Long; Addicoat, Matthew A.; Guo, Yunyu; Graf, Robert; Harano, Koji; Kikkawa, Jun; Jin, Enquan; Narita, Akimitsu; Müllen, Klaus (Journal of the American Chemical Society, 2023)
The development of highly luminescent two-dimensional covalent organic frameworks (COFs) for sensing applications remains challenging. To suppress commonly observed photoluminescence quenching of COFs, we propose a strategy involving interrupting the intralayer conjugation and interlayer interactions using cyclohexane as the linker unit. By variation of the building block structures, imine-bonded COFs with various topologies and porosities are obtained. Experimental and theoretical analyses of these COFs disclose high crystallinity and large interlayer distances, demonstrating enhanced emission with record-high photoluminescence quantum yields of up to 57% in the solid state. The resulting cyclohexane-linked COF also exhibits excellent sensing performance for the trace recognition of Fe3+ ions, explosive and toxic picric acid, and phenyl glyoxylic acid as metabolites. These findings inspire a facile and general strategy to develop highly emissive imine-bonded COFs for detecting various molecules.